THE PROBLEM OF THE WORLD AND MAN IN THE PHILOSOPHY OF B. PASCAL AND H. SKOVORODA - Синяков, С. В.; Сластенко, Е. Ф. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article deals with the problem of man and the world comparing the philosophies of B. Pascal and H. Skovoroda.